Correlation Between Management of Balanced Menu and Weight Gain on Pregnant Women Trimester III in Rural Hospital Montasik 2015 - Halimatussakdiah Halimatussakdiah (Syiah Kuala University, 2015)
The result of national economic Social survey indicatesthat there is 27.6% of pregnant women with chronic energy deficiency (KEK)who tendto havea baby with low birth weight (BBLR).Chronic energy deficiency(KEK) becomes indirect causes of pregnant mother’sdeath about 40% and another indirect cause is anemia about 37%. Moreover, in rural areasthere are 23%pregnant women deal with malnutrition. The general causes of malnutrition in pregnant women is consumingfoods that are not met by the recommended nutritional requirements. Besides, the timeof adjacent pregnancyand childbirth, and lack of education and knowledge would cause the level of maternal mortality become high. The objective of this study is to seecorrelation between management of balanced menu at the third trimester of pregnant womenandweight gain in rural hospitalMontasik in 2015. The study was descriptive correlative research with cross sectional study design. The data was collected by using purposive sampling technique involved 30 sample. Data collection was done on August 23 to July 6,2015using questionnaire.Thesecondary data is processed byunivariate and bivariate analysis. The result showed that management of balanced menu canincrease thebody weight of pregnant women (83.3%), management of balanced diet increases the circumference of the upper arm(LILA) (86.7%), and management of balanced diet increases the level of uterus Fundus (TFU) (80%). The study concludes thatthere is a correlation betweenmanagement menu andthe weight gain in the third trimester of pregnant women with p-value = 0.028 (α = 0.05). The result of this study is expected to be an input and a reference for hospital officers in maintaininghealth centerstoimprove servingqualityforpregnant women, especially in terms of management menu by measurement of weight, MUAC, and TFU whenthe pregnant womenisin Ante Natal Care (ANC).